Adversity Quotient and the Development of Students' Endurance Dimensions in the New Normal Era: A Study of Islamic Religious Education Online Learning at the State University of Malang - Mardiana, Dina (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2022)
The challenges of implementing Islamic Religious Education (Pendidikan Agama Islam-PAI) online learning in universities in the new normal era today necessitates good endurance based on Adversity Quotient (AQ) in students. This research focuses on the efforts of the State University of Malang (UM) to develop the AQ-based endurance dimension possessed by students through PAI online learning. This study composes a critical analysis through a qualitative approach and the type of case study. This research concludes that the dimension of students' endurance can develop through the three academic activities they undertake during the online learning process of PAI, namely: Tafaquh fi Diinil Islam (TDI); Bina Baca Al-Qur'an (BBQ); and Bina Ibadah (BI). In the PAI online learning process, these three activities can empirically frame the axiological framework of developing endurance dimensions for students at the State University of Malang.